Kontruksi Yuridis Hybrid Contract Dalam Pembiayaan Take Over KPR pada Perbankan Syariah - Albar, Kholid (Jurnal Justisia Ekonomika: Magister Hukum Ekonomi Syariah, 2018)
Abstract            In the process of the occurrence of hybrid contract in the process of take over of course the bank which in this case is sharia banking will certainly experience the risks in the financing that is influenced by several factors including the rate of inflation so that it also affects the liquidity of sharia banking itself, today due to the liquidity of sharia banking largely depends on the acquisition of third party funds either in the form of investment account or current account which will be channeled into financing according to sharia, such as mudharabah, musyarakah, murabaha, salam, isthisna and ijarah which can generate profit sharing margin which is the main profit source (income) of sharia banks. Lack of liquidity will cause banks to bankruptcy quickly, whereas if excess liquidity is also dangerous is a low probability that leads to the same thing. So the risk of liquidity will be a consideration for depositors to choose which bank for customers save funds. Because the purpose of this study, First to determine the effect of hybrid contract variables, inflation rate and concepts of profit sharing simultaneously and partially to liquidity risk in Islamic banking. Keywords : Hybrid Contract, Take Over dan Syariah Bank